The Najib administration's US policy : objectives, strategies and actions (2009-2016) - Muhammad Aisar bin Mohamad Yusop (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This thesis evaluates the Najib administration's US policy with regards to the economy and security for the period between 2009 and 2016. This thesis firstly identifies the external, domestic and idiosyncratic factors that affect Malaysia-US relations during the Najib administration from 2009 to 2016. Then, this thesis identifies the objectives and related strategies of the administration's US policy. The evaluation is done by qualitatively evaluating the actions and results that the Najib administration had achieved for its US policy against the objectives it had set with the effects of the external, domestic and idiosyncratic factors that were in play. This thesis based its findings on publicly-available government documents and reports, newspaper articles and an in-depth unstructured interview with a Malaysian diplomat previously based in Washington during the Najib administration. This thesis finds that the Najib administration had put much importance on Malaysia-US relations regarding the economy and security. For the economy, the administration actively pursued the Trans-Pacific Partnership Agreement (TPPA), courted US businesses to invest in Malaysia and attempted to get Malaysia into the US Visa Waiver Program. In terms of security, the Najib administration continued and enhanced existing military cooperation between Malaysia and the US. The cooperation between the security agencies of both countries had also increased. However, bilateral trade and US investment in Malaysia during the Najib administration have been slow in comparison to other countries such as China and Japan. Due to a lack of funds, the Malaysian armed forces had not made important procurement with US arms manufacturers to modernise itself. Even though Malaysia-US relations had improved diplomatically during the Najib administration, the progress on the economy and the security aspect of the relation, remains limited